Phosphatidylcholine synthesis in the developing small intestine. - Holtzapple, P G (1980)
1. Phosphatidylcholine synthesis in the foetal, newborn and adult small intestine of rats was studied by determination of cytidine diphosphocholine-1,2-diacylglycerocholine phosphotransferase (cholinephosphotransferase) and acyl-CoA-1-acyl-sn-glycerol-3-phosphocholine acyltransferase (lysophosphatidylcholine acyltransferase) activities and the incorporation of [1-14C]oleic acid into phosphatidylcholine. 2. Cholinephosphotransferase activity was low in foetal jejunum and ileum, increased 3-4 fold in the ileum by 6 days of age and by 12 days in the jejunum. Jejunal activity remained constant throughout weaning; ileal activity gradually decreased to values 25% of that of the jejunum. 3. Lysophosphatidylcholine acyltransferase activity was high in foetal jejunum and ileum, decreased 70% immediately after birth in the jejunum and increased to adult values by 12 days of age. Ileal activity decreased by 20% after birth, but decreased more rapidly at weaning to 30% of the activity in jejunum. 4. Initial rates and steady-state incorporation of [1-14C]oleic acid into phosphatidylcholine by jejunal rings of 10 day-old rats exceeded that observed in jejunal rings from adult rats by 2-4-fold. 5. In the postnatal jejunum, neither cholinephosphotransferase and lysophosphatidylcholine acyltransferase activities nor oleic acid incorporation were stimulated by cortisone administration in vivo.